DINAMIKA KEBIJAKAN PUBLIK DALAM PENGELOLAAN ASET DANAU LIMBOTO DI KABUPATEN GORONTALO - Trisusanti Lamangida (Universitas Muhammadiyah Gorontalo, 2019)
The dynamics of public policy in managing the assets of the Limboto lake area in Gorontalo Regency is the focus of this research. This article aims to analyze and explain the dynamics of public policy management of the Lake Limboto area assets. The method and approach used is descriptive qualitative. Data collection was done by purposive sampling technique (Sugiyono: 2010), observation, interviews and documentation. Data analysis was carried out following an